The Influence of Internal Control System, Information Technology Utilization, and Organizational Commitment on Government Accountability Performance - Dena Handayani; Ivan Yudianto; Nunuy Nur Afiah (Universitas Padjadjaran, 2020)
Each government institution has a mission to be achieved. Goals and objectives achievement that has been set through the system of accountability performance is a common indicator to measure mission accomplishment. There are several district and municipals in the province of West Java that has poor accountability performance. This study aims to determine the effect of the government internal control system, information technology utilization and organizational commitment on accountability performance of government institutions. The research adopts a quantitative interpretive approach. The population in this study is six districts and municipals in West Java Province, where each district and municipals consists of 5 local government working unit. The data analysis technique in this study uses multiple linear regression. The results of this study indicate that partially and simultaneously, there is a positive and significant influence between the government internal control system, information technology utilization and organizational commitment on accountability performance of government institutions.